(3GdJMdjd GdGbJUGOj Gdcdj (B:s (3CSGSjGJ (B-(3JWHjbGJ(B-(3Mdhd GdJeGQjf (B/s - (3eUWai, GMeO aQjOs ((3GdGScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2008)
(3GdLRA GdGhd COhGJ GdJMdjd GdGbJUGOj Gdcdj OGdI GdGfJGL Gdcdi , OGdI GdGSJgdGc hGdeVGYa ,OGdI GdGSJKeGQ GdLRA GdKGfj (B. (3JMOjO GdeSJhi GdJhGRfj ddGbJUGO Gdcdj GdWdH Gdcdi hGdYdQV Gdcdi , MSGH GdONd Gdbhej GdLRA GdKGdK JMOjO GdeSJhi GdJhGRfj ddGbJUGO Gdcdj echfGJ GdWdH Gdcdj , GdfGJL GdeMdj hGdONd GdTNUj GdeJGM , GdfehPL GdcdGSjcj hGdJhGRf GdGbJUGOj Gdcdj , GdfehPL GdcfRj hGdJhGRf GdGbJUGOj Gdcdj , GdGfaGb GdMchej hGdeSJhi GdJhGRfj ddGbJUGO Gdcdj , GdYdGbGJ GdOhdjI GdhGRf GdGbJUGOj Gdcdj GdLRA GdQGHY JeGQjf hMdhdgGs
(3HjHdjhZQGajG(B: (3U(B.309s
Keywords: (3GdEbJUGO GdJMdjdjs; (3GdEbJUGO Gdcdjs; (3GdONd Gdbhejs